(untitled) (Tempo e Argumento, 2022)
This paper sheds light upon some experiences occurred in a Practicum course in 2019, when a group of teachers-in-training taught classes on Indigenous History. The sources to be analyzed are comprised of teaching and research projects, lesson plans, as well as reports and articles written by the student-teachers. Classes were taught to 6th-grade students at Colégio de Aplicação – UFSC. The central issue guiding this investigation emerged from a perceived interest from the group of teachers-in-training towards the topic, and their commitment to developing the topic, with the objective to foster historical learning in their classrooms. Thus, some questions have moved this paper into motion. What choices were made when preparing these lessons? What materials were selected? And, lastly, what can be said on the task of teaching Indigenous History for Basic Education students? The teaching of Indigenous History in basic education has been mandatory since Bill 11,645/08 was passed, and its presence is also mandatory in textbooks. However, between the bill of law and the classroom there is a path beset with struggles. Therefore, this study aims at perceiving tensions regarding lesson planning and teaching by this group of teachers-in-training, as well as at pointing out potentials in this movement towards teacher education with a commitment to topics related to diversity, focused on greater plurality in curricula.